Effects of irrigation and fertilization management on kiwifruit yield, water use efficiency and quality in China: A meta-analysis - Ding, Yuehua; Shang, Chunfeng; Zhao, Long; Jin, Shanshan; Li, Chenyang; Yin, Shanshan; Ahammed, Golam Jalal (Frontiers in Plant Science, 2025)
The water-saving and fertilizer-reduction strategies is important for sustainable agricultural development. However existing kiwifruit water-saving and fertilizer-reduction studies showed significant contradictions in the results of water and fertilizer management. Studies have reported conflicting findings on irrigation: some suggest over-irrigation increases yield and WUE, while others advocate low-volume irrigation. Consequently, this study offers a comprehensive meta-analysis encompassing 1038 observations, with the objective of evaluating the influence of water management and optimized fertilization on the yield, water use efficiency (WUE), and quality of kiwifruit. The results showed that the response of kiwifruit to water management was particularly significant in areas with annual average rainfall > 800 mm and field water holding capacity > 28%, and excessive irrigation had a greater negative impact on yield and WUE. With the increase of tree age, the yield-increasing effect of kiwifruit on water and fertilizer optimization gradually weakened. In terms of irrigation methods, drip irrigation has more advantages than traditional irrigation methods. Reducing super-optimal input (SOI) water input can increase kiwifruit yield by 16.24% and WUE by 20.06%. In terms of fertilization management, reducing the input of SOI nitrogen fertilizer can significantly increase the yield of kiwifruit by 32.76%, while reducing the input of SOI nitrogen, phosphorus and potassium can increase the yield by 3.45%. The contents of soluble sugar and vitamin C increased by 6.35% and 18.37%, respectively, but the contents of titratable acid and soluble solids decreased by 4.35% and 6.18%, respectively. In addition, the optimal nitrogen fertilizer level for kiwifruit varies from region to region, and it is generally recommended to be between 100 – 105 kg/ha per hectare. In summary, scientific and reasonable water and fertilizer management can significantly improve the yield and quality of kiwifruit, optimize WUE, and reduce water and fertilizer waste, providing theoretical basis and practical guidance for sustainable agricultural development.